Learning From Picturebooks: Reading and Writing Multimodally in First Grade. (28th November 2012) - Martens, Prisca; Martens, Ray; Doyle, Michelle Hassay; Loomis, Jenna; Aghalarov, Stacy
Abstract: This article shares the authors' work with first graders and how, through various reading, writing, and art experiences around picturebooks, the children learned to read and communicate through art along with written language. The work is grounded in multimodality theory and the belief that all modes (particularly art for the purposes of this article) are equally valid and significant ways of communicating meaning. The article provides examples of experiences with the picturebooks I Love My New Toy and Guji Guji of how the children came to understand the language of art. Insights from this work that are discussed include that young children can and do think and read multimodally, that understanding art as an equally valid mode of communication, along with written language, provides children with additional pathways through which to construct meaning, and that art is a valid language that needs to be valued and taught.